Group 5 ansa-metallocenes: Structural and dynamic properties of tetrahydroborate complexes - Conway, S; Doerrer, L; Green, M; Leech, M (American Chemical Society, 2000)
The new compounds [Nb{(eta-C5H4)X(eta-C5H4)}Cl-2] (X = CEt2 1a, C(C5H10) 1b, C2Me4 1c), [Nb{(eta-(C5H3Bu)-Bu-t)C2Me4(eta-(C5H3Bu)-Bu-t)}Cl-2] 1d, [Nb{(eta-C5H4)X(eta-C5H4)}(eta(2)-BH4)] (X = CEt2 2a*, C(C5H10) 2b, C2Me4 2c*, SiMe2 2e*), [Nb((eta-(C5H3Bu)-Bu-t)C2Me4(eta-(C5H3Bu)-Bu-t)}(eta(2)-BH4)] (2d*), [Nb{(eta-C5H4)X(eta-C5H4)}(eta(2)-BD4)] (X = C2Me4 3c, CMe2 4), and [V{(eta-C5H4)C2Me4(eta-C5H4)}(eta(2)-BH4)} (5*) have been prepared. The asterisk indicates the crystal structure has been determined. The hydrogen scrambling processes in the tetrahydroborate complexes 2a-e, 3c, 4, 5, and [Nb{(eta-C5H4)CMe2(eta-C5H4)}(eta(2)-BH4)] have been studied. The free energy barrier Delta G(double dagger) to bridge-terminal hydrogen exchange is considerably reduced when the bridging unit imposes significant structural changes in the metallocene.